Platinum redistribution in the Ni0.9Pt0.1/InP system: Impact on solid-state reaction and layer morphology. (15th June 2021) - Boyer, F.; Dabertrand, K.; Gergaud, P.; Grégoire, M.; Rafhay, Q.; Rodriguez, Ph.
Abstract: In the scope of integrating III–V device contacts on a 300 mm platform, Ni-based contacts are envisioned. In this regard, the Pt redistribution in the Ni0.9 Pt0.1 /InP system, and the impact of Pt-alloying of Ni thin films on InP over solid-state reaction and layer morphology have been investigated. Results have shown that at low temperature (T  <  300 °C), the presence of Pt partially slows down the diffusion of Ni towards the InP substrate, which as a result delays the growth of an intermixing amorphous Ni–In–P layer. In addition, the presence of Pt in the system has delayed the consumption of the Ni0.9 Pt0.1 layer. At higher temperatures (T  ≥  300 °C), the thermal energy brought to the system overcomes the Pt-induced partially slowed down Ni diffusion, and the observed phase formation sequence indicates that the Ni-based crystallized phases (Ni 2 P, Ni 3 P and Ni 2 InP) are identified regardless of the presence of Pt, which is not incorporated into the formed Ni-based phases (Ni 2 P, Ni 3 P and Ni 2 InP). Instead, the latter is rejected from the forming interface, which allows it to participate to the formation of the stable Pt 3 In 7 crystallized phase.